Translation, cross-adaptation and measurement properties of the Brazilian version of the ACL-RSI Scale and ACL-QoL Questionnaire in patients with anterior cruciate ligament reconstruction - Silva, Laryssa Oliveira (2018)
Background: Scales to assess the quality of life and return-to-sport after reconstruction of the anterior cruciate ligament (ACL) may help the clinical decision-making process. Objective: To cross-culturally adapt and determine the validity of the Brazilian versions of the Anterior Cruciate Ligament Return to Sport after Injury (ACL-RSI) and the Quality of Life Questionnaire (ACL-QoL). Methods: The process of translation and cross-cultural adaptation followed the recommendations of international guidelines. One hundred participants filled out the Brazilian versions of these instruments, the Tampa Scale for Kinesiophobia (TSK), the International Knee Documentation Committee (IKDC) Subjective Knee Evaluation Form, and the 36-Item Short Form Health Survey (SF-36). The measurement properties of reliability, internal consistency and construct validity were measured. Results: The ACL-RSI and the ACL-QoL were successfully translated and cross-culturally adapted. Both questionnaires showed good test---retest reliability (ICC2,1 = 0.78, 95% CI = 0.67---0.85 for the ACL-RSI; and ICC2,1 = 0.84, 95% CI = 0.76---0.90 for the ACL-QoL) and good internal consistency (Cronbach’s alpha = 0.87 for the ACL-RSI; and Cronbach’s alpha = 0.96 for the ACL-QoL). A reasonable correlation was found between both questionnaires and the TSK, and a low to reasonable correlation was found between the questionnaires and the SF-36 in terms of validity. Compared to the IKDC Subjective Knee Evaluation Form, the ACL-RSI had a reasonable correlation and the ACL-QoL had a good correlation.